الهبة الديموغرافية وإستثمارها في التنمية الإقتصادية رؤية واقعية للعراق بعد عام 2003 - مسلم حمدية شاكر; جبر نادية لطفي (Journal of Economics and Administrative Sciences, 2019)
Abstract The relationship between population and development is one of the most interrelated relations in contemporary societies. Therefore it is important focus on the demographic aspects of the population and its integration with developmental aspects, because the population is the makers of development and responsible for its success. The population composition and their qualitative composition are important factors in development. This change in age rate is because of demographic operations which lasted for long time. The change we are talking about is happing currently in Arab countries especially in Iraq who the labor ages has been increased while children and old ages were decreased. This issue led Iraq to be known as one of the countries that has the phenomena of demographic change. According to the UN the proportion of the population under 15 years of age (30%) of the total population and that the proportion of older persons 65 and more than (15%) of the total population. This change can result available opportunities of development under the interaction and harmony among proficiency and skillful human resources. Regarding to these we need to take advantage of the demographic changes by providing jobs for un employ & enhancing their skills, Building human capital capacity, investing available resources. In order to achieve the following above we have to take in consideration the local & national obstacles & restrictions.